Nonsyndromic Split Hand/ Foot Malformation: Ectrodactyly - Ray, Sanghamitra; Jain, Prakash Chand (Journal of Nepal Paediatric Society, 2016)
The Case A three year old girl came to our OPD with deformity of left hand called ectrodactyly. She had no other deformities, dysmorphic features and was developmentally appropriate. The X-ray of the hand showed normal radius, ulna and metacarpals but absence of phalanges of the middle three fingers of left hand. She was examined in detail for any ectodermal anomaly, clefting of lip or palate. USG abdomen, kidney and urinary tract was done to rule out any urinary tract malformation. She was finally referred to higher centre for reconstructive surgery for ectrodactyly. J Nepal Paediatr Soc 2016;36(1):103-104